Cognitive Behaviour Therapy to Reduce Communication Apprehension in Students Who Are Working on Thesis - Khoirunnisa Khoirunnisa; Tri Kurniati Ambarini (Jurnal Psikologi Teori dan Terapan, 2023)
The complexity of writing a thesis causes difficulties or obstacles for students, which can result in the emergence of anxiety symptoms. This study aims to determine whether the Cognitive Behaviour Therapy (CBT) approach can reduce the level of communication apprehesion experienced by students who are working on a thesis. Study 1 used a quantitative experimental method with a non-control group design and study 2 used a qualitative method. The participants in this study were 5 students from one of the universities in Surabaya. The results of study 1 show that providing interventions in the form of group counseling with a CBT approach can reduce the level of communication apprehension experienced by students who are working on their thesis. The results of study 2 show that group members can change their cognitive distortions so that they have a more positive thought process. Group members are also able to apply CBT strategies that have been done together to reduce their communication anxiety so that it can increase the effectiveness of communication in preparing the thesis. ABSTRAK Kompleksitas penulisan skripsi menimbulkan kesulitan ataupun kendala bagi mahasiswa, yang dapat berakibat munculnya gejala-gejala kecemasan. Penelitian ini bertujuan untuk mengetahui apakah pendekatan Cognitive Behaviour Therapy (CBT) dapat menurunkan tingkat kecemasan komunikasi yang dialami oleh mahasiswa yang sedang mengerjakan skripsi. Studi 1 menggunakan metode kuantitatif eksperimen dengan non control group design dan studi 2 menggunakan metode kualitatif. Partisipan dalam penelitian ini adalah 5 orang mahasiswa dari salah satu universitas di Surabaya. Hasil studi 1 menunjukkan bahwa pemberian intervensi berupa konseling kelompok dengan pendekatan CBT dapat menurunkan tingkat kecemasan komunikasi yang dialami oleh mahasiswa yang sedang mengerjakan skripsi. Hasil studi 2 menunjukkan bahwa anggota kelompok dapat mengubah distorsi kognitifnya sehingga memiliki proses berpikir yang lebih positif. Anggota kelompok pun mampu untuk menerapkan strategi-strategi CBT yang telah dilakukan bersama untuk menurunkan kecemasan komunikasinya sehingga dapat meningkatkan keefektifan komunikasi dalam penyusunan skripsi.